Moments of the political. Kazimierz Kelles-Krauz – Between dialectic laws of history and making democracy - Marzec, Wiktor (Hybris, 2012)
Text scrutinises the political writings of early XX century Polish Marxist, Kazimierz Kelles-Krauz in the light of contemporary theories of the political. In specific peripheral conditions and due to entanglement of different struggles in the Polish Kingdom under tsarist rule there was no longer possible to refer to any firm political ground: organic unity of nation, necessary class antagonism or laws of history. Therefore, Kelles-Krauz had to face a somehow similar situation to this conceptualised by contemporary theories of hegemonic articulation, and radical democracy, as in Laclau, Mouffe or Rancière. A realistic, “agonistic” conception of democracy emerges, seen as a constant move without end, necessary assumption and eternally unfulfilled demand, taken as rivalry for temporarily occupying necessarily empty space, or agonism canalising regressive drives in political way and mediating between particularisms. In a constant move of change Marxism is only one step, right and somehow necessary, but in any case the last; it certainly do not bring any closure of fully realised society. Although still in a crust of older structures of thinking and above all philosophical language, we can see in Kelles-Krauz merging of a new paradigm of political thinking, or kind of disclosure of ultimate brake or gap in political and social order. Therefore we can look also for the depictions of radical, necessary contingency present in constituting of society, so to say, moments of the political.